HYPOGLYCEAMIC ACTIVITY OF FRACTIONS OF ETHYL ACETATE FRACTION OF THE WATER EXTRACT OF ARTOCARPUS HETEROPHYLLUS SENESCENT LEAVES - Fernando, K.S.S.P.; Abeysekera, *A.M.; Padumadasa, C.; Goonathilake, A.K.E.; Choudhary, M.I.; Rahman, M.H.; Thadani, V.M.; Chandrika, U.G. (International Journal of Ayurveda and Pharma Research, 2017)
The aqueous extract of the senescent leaves of Artocarpus heterophyllus is traditionally used in Sri Lanka as a hypoglyceamic agent. It has been previously reportedthat the hypoglyceamic activity lies in the ethyl acetate fraction of the water extract (EA/W). The EA/W fraction was fractionated by chromatography on sephadex LH-20. Five fractions eluting with the following solvent systems were obtained. Fraction 1, dichloromethane/ hexane (4:1), Fraction 2, dichloromethane/acetone (3:2), Fraction 3, dichloromethane/ acetone (1:4), Fraction 4, dichloromethane/ methanol (1:1) and Fraction 5, methanol. These fractions were screened for in vivo hypoglyceamic activity. Each fraction was tested for its effect on the blood glucose levels of fasted normal and diabetic rats. None of the fractions caused hypoglyceamia on normal rats. However there was significant (p < 0.001) reduction in the blood glucose level during the first three hours after giving the fractions 3, 4 and 5 to diabetic rats. Among the three fractions fraction 4 showed the highest hypoglyceamic activity. Fractions 3, 4 and 5 were also the most active in the glucose tolerance test carried out on both normal and diabetic rats. However fraction 3 showed the highest activity in this assay. In both assays using diabetic rats fractions 3, 4 and 5 at 50 mg/kg body weight showed activity of the same order as glibenclamide at 5 mg/ kg body weight. These results maybe of potential use for the development of an anti diabetic drug from leaves of Artocarpus heterophyllus.